Effects of cross-training. Transfer of training effects on VO2max between cycling, running and swimming - Tanaka, H. (Sports Medicine, 1994)
Cross-training is a widely used approach for structuring a training programme to improve competitive performance in a specific sport by training in a variety of sports. Despite numerous anecdotal reports claiming benefits for cross-training, very few scientific studies have investigated this particular type of training. It appears that some transfer of training effects on maximum oxygen uptake (VO2max) exists from one mode to another. The nonspecific training effects seem to be more noticeable when running is performed as a cross-training mode. Swim training, however, may result in minimum transfer of training effects on VO2max. Cross-training effects never exceed those induced by the sport-specific training mode. The principles of specificity of training tend to have greater significance, especially for highly trained athletes. For the general population, cross-training may be highly beneficial in terms of overall fitness. Similarly, cross-training may be an appropriate supplement during rehabilitation periods from physical injury and during periods of overtraining or psychological fatigue.